Auditory dysfunction in patients with Huntington's disease. Issue 10 (October 2017) - Profant, Oliver; Roth, Jan; Bureš, Zbyněk; Balogová, Zuzana; Lišková, Irena; Betka, Jan; Syka, Josef
Highlights: Huntington's disease (HD) causes deterioration of speech in noise perception. Impairment of speech perception in HD correlates with deterioration of cognitive and motor functions. Auditory examination shows minimal peripheral, but pronounced central pathology of patients with HD. Abstract: Objective: Huntington's disease (HD) is an autosomal, dominantly inherited, neurodegenerative disease. The main clinical features are motor impairment, progressive cognitive deterioration and behavioral changes. The aim of our study was to find out whether patients with HD suffer from disorders of the auditory system. Methods: A group of 17 genetically verified patients (11 males, 6 females) with various stages of HD (examined by UHDRS – motor part and total functional capacity, MMSE for cognitive functions) underwent an audiological examination (high frequency pure tone audiometry, otoacoustic emissions, speech audiometry, speech audiometry in babble noise, auditory brainstem responses). Additionally, 5 patients underwent a more extensive audiological examination, focused on central auditory processing. The results were compared with a group of age-matched healthy volunteers. Results: Our results show that HD patients have physiologic hearing thresholds, otoacoustic emissions and auditory brainstem responses; however, they display a significant decrease in speech understanding, especially under demanding conditions (speech in noise) compared to age-matched controls. Additional auditory tests also show deficits in sound source localization, based on temporal and intensity cues. We also observed a statistically significant correlation between the perception of speech in noise, and motoric and cognitive functions. However, a correlation between genetic predisposition (number of triplets) and function of inner ear was not found. Conclusions: We conclude that HD negatively influences the function of the central part of the auditory system at cortical and subcortical levels, altering predominantly speech processing and sound source lateralization. Significance: We have thoroughly characterized auditory pathology in patients with HD that suggests involvement of central auditory and cognitive areas.